Konsep Nilai Pendidikan dan Moderasi Beragama dalam QS. Al-Baqarah Ayat 143: Studi Komparatif Tafsir Katsir dan Tafsir Jalalain - Nurfitriah, Nurfitriah; Anjar, Gunawan; Paramansyah, Arman (Transformasi Manageria: Journal of Islamic Education Management, 2024)
This research aims to understand and analyze the concept of the value of education and religious moderation in Al-Baqarah verse 143 according to the interpretation of Ibn Katsir and the interpretation of Jalalain. Look for similarities and differences between the two. This research uses Syafrida’s method (2021) there are a comparative descriptive qualitative method with literature study, with data collection techniques namely through observation, library or literature study and documentation, and the data analysis techniques used are data collection, data reduction, data presentation and conclusions or verification. The results of this research are that the concept of educational values ​​and religious moderation in QS. Al-Baqarah verse 143 according to Jalalain's interpretation, including at-Tawassuth, al-I'tidal, at-Tasamuh, ash-Shura, al-Islah, al-Qudwah, al-Muwathanah, al-La 'Urf, al-I' tiraf bil Urf, a justice and development. As well as having similarities and differences, including, 1) National commitment can be instilled with multireligious and multicultural values, 2) Non-violence can be instilled through a gentle attitude, 3) An attitude of tolerance in QS. Al-Baqarah verse 143 provides an understanding of how to invite good and true Islam and 4) Acceptance of local traditions can be achieved through cultural acculturation such as activities that contain the values ​​of Islamic teachings in them.